The Effects of Dietary Inclusion of Probiotic Protexin on Egg Yield Parameters of Japanese Quails (Coturnix coturnix Japonica) - Ayasan, Tugay; Ozcan, Bahri Devrim; Baylan, Mikail; Canogullari, Sibel (International Journal of Poultry Science, 2006)
The present study was conducted to investigate the effects of grower diets, dietary three different levels of probiotic (protexin) in grower diet on egg production parameters and egg shell quality of Japanese quail (Coturnix coturnix Japonica). In this study, 225 female Japanese quails were used. The experimental quails were divided into three dietary groups of similar mean weight comprising 75 birds each, consisted of 3 subgroup containing 25 birds each. Treatment groups were assigned control Group A (unsupplemented diet), Group B (0.5 kg per tonne `Protexin` supplemented diet) and Group C (1.0 kg per tonne `Protexin` supplemented diet) for 5 weeks. After 5 weeks, probiotic treatment was ceased and then all groups were allowed to nourish standard layer diet. Results showed that age and body live weight of quails at the first laying was found significant (P< 0.05) but the first 10 eggs weight and shape index of the first 10 eggs were not found significant (P>0.05) different between groups. During the egg production period, probiotic supplementation to the diet did not affect feed intake, feed conversion efficiency, average egg weight, egg shell thickness and egg shape index (P>0.05), but affected egg production and egg shell weight (P< 0.05).